1994
DOI: 10.2172/10137382
|View full text |Cite
|
Sign up to set email alerts
|

Dose rate estimates from irradiated light-water-reactor fuel assemblies in air

Abstract: This is an informal report intended primarily for internal or limited external _ .``_x ._)'Q`LK`,(_`.`_ distribution.The opinions and conclusions stated are those of the author and may or may not be those of the Laboratory. Work performed under the auspices of the U.S. Department of Energy by the Lawrence Livermore National Laboratory under Contract W-7405-Eng-48. I ' M DISCLAIMER This document was prepared as an account of work sponsored by an agency of the United States Government.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Even 50 years after discharge, the radiation level from penetrating gamma rays a meter away from an assembly of spent light water-reactor fuel rods is 5 to 10 Sieverts/hour-enough to assure a lethal dose in less than an hour (18). By comparison, virtually all of the radiation from separated plutonium is short-range alpha particles (helium nuclei), which cannot even penetrate human skin.…”
Section: Tradeoffsmentioning
confidence: 99%
“…Even 50 years after discharge, the radiation level from penetrating gamma rays a meter away from an assembly of spent light water-reactor fuel rods is 5 to 10 Sieverts/hour-enough to assure a lethal dose in less than an hour (18). By comparison, virtually all of the radiation from separated plutonium is short-range alpha particles (helium nuclei), which cannot even penetrate human skin.…”
Section: Tradeoffsmentioning
confidence: 99%
“…The predicted radiation gamma dose rate is a key parameter to determine if a spent nuclear fuel assembly is self-protected from misuse as well as an indicator for worker/inspector safety. Recent studies [1,2,3] showed that using state-of-the-art techniques for dose rate calculations, including the one adopted for this study, the numerical calculations of the gamma dose rates are three times lower than those from the most commonly-cited reference values for spent LWR fuel [4] used by domestic and international agencies. With only a few publically available experimental data points worldwide for this type of benchmark study, the gamma flux measurements from the Spent Fuel Non Destructive Assay (NDA) measurement campaign can be used to help validate the physics approach used in calculating gamma dose rates [5].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to accurately predict the dose rates from the spent nuclear fuel assembly is very important for assessing its self-guard and self-protection properties. Previous studies showed that the direct numerical calculations of the dose rates gave a much lower value [1] than the reference value which was calculated using the gamma buildup factors [2]. In the reference calculations, the gamma dose rate through air were predicted at 1 meter away from PWR spent nuclear fuel assemblies with 33 MWd/kg burnup and 30 years of cooling time.…”
Section: Introductionmentioning
confidence: 99%